Quantitative Evaluation of Laryngopharyngeal Reflux with Reflux Finding Score (RFS). - Shamas, Irfan UL (International Journal of Human and Health Sciences (IJHHS), 2019)
Introduction: Laryngopharyngeal reflux (LPR) also known as extra esophageal reflux disease refers to retrograde flow of gastric contents to the upper aero-digestive tract. Belafsky, Postma, and Koufman have developed the reflux finding score (RFS) to diagnose LPR. My aim was to test the score in patients with LPR to reveal the validity and effectiveness of present medical management based on changes in RFS. Materials and Methods: One hundred patients with LPR were examined prospectively in District Hospital Pulwamawith 70 degree Hopkins endoscope and RFS was evaluated both before start and completion of a set medical management with lifestyle modifications. 76.7% patients reported symptomatic improvement after one month of treatment. There was no significant quantitative decrease in RFS after one month of treatment. Conclusion: Based on this study RFS is a reliable and quantitative system to evaluate and follow up patients at the time of diagnosis and subsequent evaluation after therapy. International Journal of Human and Health Sciences Vol. 03 No. 02 April’19. Page: 105-108